2019
DOI: 10.1145/3366016
|View full text |Cite
|
Sign up to set email alerts
|

Female Performance and Participation in Computer Science

Abstract: The change in the English computing curriculum and the shift towards computer science (CS) has been closely observed by other countries. Female participation remains a concern in most jurisdictions, but female attainment in CS is relatively unstudied. Using the English national pupil database, we analyzed all exam results (n = 5,370,064) for students taking secondary school exams in 2016, focusing on those students taking GCSE CS (n = 60,736), contrasting this against ICT (n = 67,359). Combining gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
2
8
0
1
Order By: Relevance
“…However, the removal of the ICT qualification in the UK has resulted in a decline in computing provision in English schools, in terms of both hours being taught and qualifications achieved by students (Kemp et al, 2019). The data from examination sittings also indicates that the change of subject content is having a particularly negative impact on the participation and attainment of young women in computing (Kemp et al, 2019). Perhaps a similar path is being followed in Ireland; in a survey conducted in 2019, it was found that while 38% of the teachers teaching the subject were women, only 22% of the students taking it were women (LERO, 2019).…”
Section: Global Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the removal of the ICT qualification in the UK has resulted in a decline in computing provision in English schools, in terms of both hours being taught and qualifications achieved by students (Kemp et al, 2019). The data from examination sittings also indicates that the change of subject content is having a particularly negative impact on the participation and attainment of young women in computing (Kemp et al, 2019). Perhaps a similar path is being followed in Ireland; in a survey conducted in 2019, it was found that while 38% of the teachers teaching the subject were women, only 22% of the students taking it were women (LERO, 2019).…”
Section: Global Contextmentioning
confidence: 99%
“…The move to computer science is analogous to what has happened in Ireland. However, the removal of the ICT qualification in the UK has resulted in a decline in computing provision in English schools, in terms of both hours being taught and qualifications achieved by students (Kemp et al, 2019). The data from examination sittings also indicates that the change of subject content is having a particularly negative impact on the participation and attainment of young women in computing (Kemp et al, 2019).…”
Section: G Lobal Conte X Tmentioning
confidence: 99%
“…Keeping in view the growing challenges of making the right career choice and the importance of appropriate career decisions, social scientists have been paying attention to the various facets involved in career selection and development. The number of studies dealing exclusively with female career development is huge, but to name just a few, (see Angervall, 2018;Arif & Ejaz, 2017;Eikhof, 2016;Kemp, Wong, & Berry, 2019;Masood, 2019). Gender studies scholars have been investigating the career choice phenomenon through the lens of feminist theories and issues related to sexism, gender discrimination, gender stereotypes, gendered role responsibilities etc.…”
Section: Literature Review Language Perception and Career (Constructs)mentioning
confidence: 99%
“…On the contrary, boys are perceived to have advantage over girls in mathematics achievement. However, evidence suggests that boys generally receive more attention from teachers and dominate in the use of equipment in science, technology and computer studies than girls ( [31,32,33,34]). Generally, boys are reinforced for intellectual pursuits and girls for nurturing activities while attributing failure in boys to lack of motivation, and girls as lacking ability ( [35,36,26]).…”
Section: Introductionmentioning
confidence: 99%